Decoupling of Pore Water Chemistry, Bacterial Community Profiles, and Carbonate Mud Diagenesis in a Land-Locked Pool on Aldabra (Seychelles, Indian Ocean). Issue 9 (1st September 2022) - Fussmann, Dario; von Hoyningen-Huene, Avril J. E.; Reimer, Andreas; Schneider, Dominik; Karius, Volker; Riechelmann, Sylvia; Pederson, Chelsea; Swart, Peter K.; Daniel, Rolf; Arp, Gernot
Abstract: Comparative pore water-sediment studies are crucial to trace biogeochemical and early diagenetic interactions between mineral and fluid phases. They are commonly conducted in stable environments with long-time diagenetic reactions between sediment and pore water. In contrast, this work presents a comparative study within the Cinq Cases pool system, a shallow and saline water body, with occasional marine influx and short-time diagenetic reactions between sediment and pore water. Cinq Cases is located on the Aldabra atoll in the western Indian Ocean. Sediments span ca. 3800 years and indicate three environmental stages: (i) An initial, at least temporary anoxic, palustrine environment, including meteoric diagenesis (Unit III), (ii) slow marine flooding, with cyanobacteria and sponge blooms (Unit II), and (iii) lagoon flooding, including oxic conditions within the sediment (Unit I). Such frequent changes in diagenetic environments of small water bodies can be retraced by three different proxies representing partially overlapping but different time scales: (i) sediments reflect ancient processes (ii) pore waters are influenced by recent processes, and (iii) bacterial communities reflect an overlay of ancient and recent processes.